COMPOSIÇÃO BROMATOLÓGICA DA POLPA DA GUAVIRA (Campomanesia adamantium) ORIUNDA DO CERRADO PANTANAL - DIONIZIO, Bruna Gasparini; GONÇALVES, Giovana de Arruda Castelo; SALMAZZO, Gustavo Ruivo; AVALHAES FILHO, Vande Roberto; CANCIO, Priscila Ferreira; PASQUETTI JUNIOR, Tiago (ANAIS DO ENIC, 2018)
-